Genotoxicity and cytotoxicity of mineral trioxide aggregate and regular and white Portland cements on Chinese hamster ovary (CHO) cells in vitro - Ribeiro, D. A.; Sugui, M. M.; Matsumoto, M. A.; Duarte, MAH; Marques, MEA; Salvadori, Daisy Maria Favero [UNESP] (Mosby, Inc, 2006)
Objective. Recently, mineral trioxide aggregate (MTA) and Portland cement have been used in dentistry as root-end-filling materials. However, the reported results concerning the biocompatibility of these materials are inconsistent. The goal of this study was to examine the genotoxicity and cytotoxicity of MTA and Portland cements in vitro by the single-cell gel (comet) assay and trypan blue exclusion test.Study design. Chinese hamster ovary (CHO) cells were exposed to MTA and regular and white Portland cements at final concentration ranging from 1 to 1000 mu g/mL for 1 h at 37 degrees C.Results. All compounds tested did not show genotoxic effects in all concentrations evaluated. No significant differences (P > .05) in cytotoxicity were observed for all compounds tested.Conclusions. Taken together, our results suggest that MTA and Portland cements are not genotoxins and are not able to induce cellular death.